Morphohistological study of the venom gland in workers of the ant Pachycondyla striata F. Smith (Hymenoptera : Ponerinae) - Ortiz, G.; Camargo-Mathias, M. I. (California State University, 2003)
Themorphology of the venom gland in workers of the ant Pachycondyla striata (F. Smith) (Hymenoptera: Ponerinae) consists of an elongated sac that is directly connected to the sting apparatus. Three distinct regions compose this gland: the external secretory portion, composed by a secretory filament that bifurcates to originate another two; the internal secretory portion, which is represented by the convoluted gland from which rises the excretory duct that liberates the venom; and the storage portion, consisting of a large sac-shaped reservoir. The histology showed that the gland possesses a strong musculature on its distal third. Underneath these muscle layers, we noted the presence of an epithelium that envelops the internal wall of the reservoir. The presence of a convoluted gland as well as secretion inside the reservoir was also noted.
Keywords: Ponerinae; ants; venom gland; morphology; convoluted gland; histology